Evaluasi Efisiensi Turbin Gas PLTGU Muara Tawar Pasca-Overhaul - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Rahardianto Ramadhan (JTM : JURNAL TEKNIK MESIN, 2026)
Gas turbine performance in a combined-cycle power plant is strongly affected by compressor condition, combustion stability, turbine expansion efficiency, and fuel consumption. This study evaluates the effect of minor-inspection overhaul on the gas turbine efficiency of Block 4 Unit 1 at PLTGU Muara Tawar using performance-test data at 137 MW before and after overhaul. The method applies Brayton-cycle calculations by processing inlet and outlet temperature, pressure ratio, air and fuel mass flow, compressor work, turbine work, heat input, back work ratio, heat rate, and component efficiency. The results show that overhaul improved the main performance indicators. Thermal efficiency increased from 32.85% to 32.93%, compressor efficiency from 90.96% to 91.58%, combustion chamber efficiency from 96.94% to 97.08%, and turbine efficiency from 90.42% to 90.48%. Heat rate decreased from 10,957.89 kJ/kWh to 10,930.15 kJ/kWh. The improvement was associated with air-intake filter restoration, compressor inlet guide vane cleaning and recoating, combustion chamber repair, burner maintenance, and turbine blade replacement. Therefore, minor inspection contributed to restoring gas turbine performance, although periodic monitoring of heat rate, compressor fouling, exhaust temperature, and fuel-air ratio is still required